No impact on long-term survival of prolonged ICU stay and re-admission for patients undergoing cytoreductive surgery with HIPEC. Issue 6 (June 2016) - Wallet, F.; Maucort Boulch, D.; Malfroy, S.; Ledochowski, S.; Bernet, C.; Kepenekian, V.; Passot, G.; Vassal, O.; Piriou, V.; Glehen, O.; Friggeri, A.
Abstract: Background: Cytoreductive surgery (CRS) and Hyperthermic intraperitoneal chemotherapy (HIPEC) are promising new approaches of peritoneal metastases. However these surgical procedures are associated with a high morbidity rate thus intensive care (IC) management following serious complications may be warranted for these patients. The impact of the prolonged IC stay or re-admission on long-term survival remains unknown. Methods: We retrospectively analysed 122 consecutive HIPEC procedures over a one year period (2010–2011) in a single academic hospital. We analysed complications that would lead to prolonged stay or re-admission into ICU and analysed long term follow-up in patients whether they required intensive care (ICU group) or not (Control group). Results: ICU group represented 26.2% of the cohort mainly due to septic or haemorrhagic shock. Among them acute kidney injury and respiratory failure were present in 50% and 47% respectively. Cohort overall mortality rate was of 5.7%. Patients were followed for 4 years and survival analysis was performed adjusting for main confounding factors in a Cox survival model. Survival was not different between groups, with a median survival of 38 months [32; 44] vs. 33 months [26; 39] in the ICU group and Control group respectively. Conclusion: Prolonged stay or re-admission into ICU does not seem to statistically impact long term prognosis of patients undergoing CRS with HIPEC.